Performance of the Regional Development Banks in Indonesia: An Application of Camel and Anova Test - Sengkey, Marthen (JBE (Journal of Business and Economics); Volume 9 No.1, 2010 JBE UNKLAB, 2010)
The study employs CAMEL model to investigate the performance of 26 state banks in Indonesia from 1994 to 2004. CAMEL results indicate that there are two (2) banks (BPDCJ and BPDWK) that do not have a good financial performance, not even one of the CAMEL ratios. In terms of assets quality ratios, there are 17 banks that have shown a good financial performance, 11 banks in terms of management quality ratio, 13 banks in terms of earning ratios, and nine (9) banks in terms of liquidity ratio. Moreover, the result shows that a bank with the best financial performance in one ratio does not automatically have a good financial performance with other ratios Furthermore, ANOVA test shows that there is no significant difference at acceptance level of 0.01, 0.05 and 0.10 among CAMEL ratios of all sample banks. This further suggests that all banks have shown statistically the same level of financial performance as evident in their CAMEL indicators. The result of the ANOVA – test is consistent with the theory that any single ratio does not provide a sufficient information from which to judge the overall performance of a firm (Gitman, 2000).